MOTIVASI PEREMPUAN BATAK TOBA BERPENDIDIKAN TINGGI DI BANDUNG - Denada Ferita Sihite, - (2022)
Batak Toba people have a philosophy of life called dalihan na tolu which functions to regulate roles and status. Likewise with the role and status of Toba Batak women who have been constructed to become subalterns. But now, many Batak Toba women have been educated to be able to have jobs and high social status. Through this study, researchers want to find out how the process of higher education motivation is able to form in Batak Toba women in the midst of traditional customs that are still firmly held. This study uses a qualitative approach and case study method on nine key participants and five supporting participants consisting of parents and traditional administrators. The location of this research is Bandung Bandung area. In collecting data in the field, researchers conducted interviews, observations, and literature studies. The results of data collection were then analyzed through the stages of data reduction, data presentation and drawing conclusions to be discussed as research results. From the results of the study, it is known that (1) the ability of Toba Batak women to have a higher education is due to the fulfillment of needs that cause motivation to be educated (2) the educational background of women has a good impact on their careers, socially and also their position in adat. ; (3) there are factors that influence the motivation of highly educated Batak Toba women which are grouped into two, namely external and internal factors.